On the study of analogue network coding for multi-pair, bidirectional relay channels - Chee, Leow Yen (Institute of Electrical and Electronics Engineers Inc., 2011)
We consider a scenario where multiple pairs of users exchange information within pair, with the help of a dedicated multi-antenna relay. The protocol integrates the idea of analogue network coding in mixing two data streams originating from the same user pair, together with the spatial multiplexing of the data streams originating from different user pairs. The key feature of the protocol is that it enables both the relay and the users to participate in interference cancellation. We propose several beamforming schemes for the multi-antenna relay and evaluate the performance using information theoretical metrics such as ergodic capacity, outage probability and diversity and multiplexing tradeoff. Analytical and simulation results justify that the ergodic capacity, outage probability and diversity and multiplexing tradeoff of the proposed beamforming schemes outperform comparable schemes.